Acute effects of exercise on the inflammatory state in patients with idiopathic pulmonary arterial hypertension - Harbaum, Lars; Renk, Emilia; Yousef, Sara; Glatzel, Antonia; Lüneburg, Nicole; Hennigs, Jan K.; Oqueka, Tim; Baumann, Hans J.; Atanackovic, Djordje; Grünig, Ekkehard; Böger, Rainer H.; Bokemeyer, Carsten; et al. (BMC pulmonary medicine, 2016)
Exercise training positively influences exercise tolerance and functional capacity of patients with idiopathic pulmonary arterial hypertension (IPAH). However, the underlying mechanisms are unclear. We hypothesized that exercise modulates the activated inflammatory state found in IPAH patients.